Placebo effect in pharmacological management of fibromyalgia: a meta-analysis. Issue 1 (23rd July 2021) - Migliorini, Filippo; Maffulli, Nicola; Eschweiler, Jörg; Betsch, Marcel; Tingart, Markus; Colarossi, Giorgia
Abstract: Introduction: The management of fibromyalgia involves a combination of pharmacological and non-pharmacological treatments. Source of data: Recently published literature in PubMed, Google Scholar and Embase databases. Areas of agreement: Several pharmacological and non-pharmacological strategies have been proposed for the management of fibromyalgia. However, the management of fibromyalgia remains controversial. The administration of placebo has proved to be more effective than no treatment in many clinical settings and evidence supports the 'therapeutic' effects of placebo on a wide range of symptoms. Areas of controversy: The placebo effect is believed to impact the clinical outcomes, but its actual magnitude is controversial. Growing points: A meta-analysis comparing pharmacological management versus placebo administration for fibromyalgia was conducted. Areas timely for developing research: Drug treatment resulted to be more effective than placebo administration for the management of fibromyalgia. Nevertheless, placebo showed a beneficial effect in patients with fibromyalgia. Treatment-related adverse events occurred more frequently in the drug treatment. Level of evidence: I, Bayesian network meta-analysis of double-blind randomized clinical trials.